Information seeking by female apparel consumer educators in Vanderbijlpark during the fashion decision-making process - van Staden, Johanna (My University, 2013)
Fashion information is sought during the fashion decision-making process and can be obtained from various sources such as magazines, fashion consultants, websites, store displays as well as personal communication. Various levels, methods such as internal and external search and types of information at the point of purchase, for example garment characteristics, price, brand, labels, social evaluation, impersonal communication with sales persons and perceived risks are used to assist the consumer in making informed fashion decisions. The broad research aim of this study was to determine which methods, sources and economics of fashion information are used and which types of fashion information at the point of purchase are sought by female educators in Vanderbijlpark during the fashion decision-making process, and to whlch extent, as well as to determine the frequency of use of various types of stores for fashion purchases. A self-administered, structured questionnaire was used to collect the data. Section A measured methods of information seeking, section B determined the economics of information search, section C investigated sources of fashion information and section D determined types of information sought at the point of purchase. Demographic information and the frequency with which clothing was bought at various store types were investigated in Section E. A random sample was chosen from the female educating staff of the 22 schools in Vanderbijlpark. The majority of the educators (40.18 percent) were between the ages of 41 and 50, representing baby boomers. Almost all (95.5 percent) had a tertiary qualification and most were married. Regarding the methods of information seeking, the respondents depended on internal information seeking more than on external methods and were moderately involved in the process. Shopping in stores was regarded the most important source of fashion information. Garment characteristics, namely fit and comfort, were regarded as the most important types of information at the point of purchase, while the most popular type of store was department stores, followed by specialty and discount stores. Four clusters of respondents could be distinguished, each with a specific disposition towards the methods and economics of search, sources used and types of information sought at the point of purchase during the fashion decision-making process.
Thesis (M. Tech. (Fashion, Dept. of Visual Arts and Design)--Vaal University of Technology.
Keywords: Fashion information; Choice of clothes; Shopping for clothes; 391.096822; Clothing trade -- South Africa; Retail trade -- South Africa; Fashion merchandising -- South Africa